Import Function for Nigeria from 1980 - 2014 - Ebere, Edith Chidinma (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2016)
This research work aims at investigating import as a function of income in Nigerian economy between 1980 and 2014. The econometric techniques used for this thesis are Unit Root Tests, Johansen Cointegration, Vector Error Correction, and Granger Causality Methods. These techniques were consistent with seven of the previous studies in the literature review, and the other seven previous studies used other econometric techniques in their papers. Annual time series data was taken from the World Bank Database. The regression model was in logarithms transformation form purposely to linearize the model, to reduce the impact of outliers and thus to avoid spurious regression result. The theoretical expectation is that there is a positive relationship between the IMPORTS and GNI, in Nigeria, that is, the higher is the GNI, the higher will be the consumption and thus the import. One Other variable was introduced to independent variable and the other variable is Real Exchange Rate (REXR). (IMPORTS), (GNI) and (REXR) have Unit Roots problem at level but were stationary at first difference statistics. Furthermore, in an investigation of cointegration, Trace and Max. Eigen Value Test indicates one cointegrating equations at 5% significance level. This thesis shows that there is a long-run relationship between the Imports and the Income in Nigeria between 1980 and 2014. The long-run shows positive relationship while the short-run shows no significant relationship.

ÖZ: Bu araştırma, 1980 ile 2014 yılları arasında Nireya ekonomisine ait İthalat fonksiyonunu tahmin etmeye yönelik bir çalışmadır. Kullanılan ekonometrik teknikler Unit Root Test, Cointegration, Vector Error Correction and Granger Causality metotlarıdır. Bu yönüyle, bu çalışma önceki 7 çalışma ile benzerlik, ve diğer 7 çalışmayla da farklılık göstermektedir. Araştırma 35 yıllık Nijerya verilerini kullanmaktadır ve bu verilerin tümü Dünya Bankası veri tabanından elde edilmiştir. Verilerin tümü logaritmik veri olarak kullanılmıştır. Burdaki amaç, modeli linearize etmek, outlier etkisini azaltmak ve genel olarak yanıltıcı regresyon sonuçlarını önlemekti. Teorik beklenti, İthalat ile Milli Gelir arasında positif bir ilişki olması yönündedir. Bir başka deyişle, gelir arttıkça tüketim artmakta ve buna bağlı olarak da ithalat artmaktadır. Regresyonda kullanılan bir diğer değişken ise Reel Döviz Kurudur. Her üç veri de de unit root problemi vardır ve sadece ilk farkları (fırst differenced data) stationary ‘dir. Trace ve Max Eigen değerleri bir tane cointegrating denklem olduğunu göstermektedir. Yapılan regresyon gelir ile ithalat arasında uzun vadede positif bir ilişki olduğunu göstermektedir. Bu da teorik beklentimizle uyumludur.
Master of Science in Economics. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Economics, 2016. Supervisor: Assoc. Prof. Dr. Çağay Coşkuner.
Keywords: Economic Conditions and Development-Nigeria; Stationary; Cointegration; VECM; Granger Causality; Import; Income; Economics